Antiviral efficacy of Andrographis paniculata and andrographolides: A narrative review - Kumarappan Chidambaram (Asian Pacific Journal of Tropical Biomedicine)
The rise of emerging infectious diseases has become notably prominent due to ecological changes and mutations in pathogens. The respiratory illness outbreak caused by the COVID-19 pandemic has spread globally. Natural products contain numerous structures and biological activities, offering ample options for discovering new antiviral drugs with unique targets and mechanisms. Andrographis paniculata has been utilized in Indian Ayurvedic, Swedish, Traditional Thai, and Chinese medicine to alleviate coughs, colds, and influenza symptoms. Early-stage laboratory studies indicate that this herbal extract may reduce inflammation and fever, and boost the body’s natural defenses against viruses, potentially leading to symptom relief. This review aims to systematically present clinical trial data about antiviral herbal formulations derived from Andrographis paniculata, delineating the antiviral effects of both natural and synthetic derivatives, along with in silico analyses.